Cinema, gender and history: representations of the body and sexualization in Suicide Squad - Ribas, Fernanda; Pereira, Bruno César (Temporalidades, 2021)
Cinema is considered an accessible, respectable and captivating form of entertainment with the ability to propagate information, representations, ideologies and / or naturalize situations. And yet, cinema, through its productions, has gained in recent decades the status of historical source. Throughout this text, starting from the approaches of gender studies, we will analyze the film Suicide Squad (2016), based on comics, by director David Ayer. Our proposal will focus on the representation and characterization of one of the characters in this work, Harley Quinn (Margot Robbie), who was represented with exaggeratedly sexual characteristics and, also, to highlight some situations where the representation of the woman is seen only as an object of desire besides its unbelief in the world of comics. Thus, we aim to show that there is a need to review and change the way women are treated and represented in the film industry and in comic drawings, because, as presented, cinema has a great influence on the construction of representations and perpetualizations of social imaginary.